Comparing local and systemic control between partial-and whole-breast radiotherapy in low-risk breast cancer—a meta-analysis of randomized trials - Haussmann, Jan; Budach, Wilfried; Strnad, Vratislav; Corradini, Stefanie; Krug, David; Schmidt, Livia; Tamaskovics, Bálint; Bölke, Edwin; Simiantonakis, Ioannis; Kammers, Kai; Matuschek, Christiane (Cancers, 2021)
Purpose/Objective: The standard treatment for localized low-risk breast cancer is breast-conserving surgery, followed by adjuvant radiotherapy and appropriate systemic therapy. As the majority of local recurrences occur at the site of the primary tumor, numerous trials have investigated partial-breast irradiation (PBI) instead of whole-breast treatment (WBI) using a multitude of irradiation techniques and fractionation regimens. This meta-analysis addresses the impact on disease-specific endpoints, such as local and regional control, as well as disease-free survival of PBI compared to that of WBI in published randomized trials. Material and Methods: We conducted a systematic literature review and searched for randomized trials comparing WBI and PBI in early-stage breast cancer with publication dates after 2009. The meta-analysis was based on the published event rates and the effect sizes for available oncological endpoints of at least two trials reporting on them. We evaluated in-breast tumor recurrences (IBTR), local recurrences at the primary site and elsewhere in the ipsilateral breast, regional recurrences (RR), distant metastasis-free interval (DMFI), disease-free survival (DFS), contralateral breast cancer (CBC), and second primary cancer (SPC). Furthermore, we aimed to assess the impact of different PBI techniques and subgroups on IBTR. We performed all statistical analyses using the inverse variance heterogeneity model to pool effect sizes. Results: For the intended meta-analysis, we identified 13 trials (overall 15,561 patients) randomizing between PBI and WBI. IBTR was significantly higher after PBI (OR = 1.66; CI-95%: 1.07–2.58; p = 0.024) with an absolute difference of 1.35%. We detected significant heterogeneity in the analysis of the PBI technique with intraoperative radiotherapy resulting in higher local relapse rates (OR = 3.67; CI-95%: 2.28–5.90; p < 0.001). Other PBI techniques did not show differences to WBI in IBTR. Both strategies were equally effective at the primary tumor site, but PBI resulted in statistically more IBTRs elsewhere in the ipsilateral breast. IBTRs after WBI were more likely to be located at the primary tumor bed, whereas they appeared equally distributed within the breast after PBI. RR was also more frequent after PBI (OR = 1.75; CI-95%: 1.07–2.88; p < 0.001), yet we did not detect any differences in DMFI (OR = 1.08; CI-95%:0.89–1.30; p = 0.475). DFS was significantly longer in patients treated with WBI (OR = 1.14; CI-95%: 1.02–1.27; p = 0.003). CBC and SPC were not different in the test groups (OR = 0.81; CI-95%: 0.65–1.01; p = 0.067 and OR = 1.09; CI-95%: 0.85–1.40; p = 0.481, respectively). Conclusion: Limiting the target volume to partial-breast radiotherapy appears to be appropriate when selecting patients with a low risk for local and regional recurrences and using a suitable technique.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Breast cancer; Local recurrence; Partial-breast treatment; Radiotherapy